Allotwinning in a molecular crystal: (1R, 3S)‐dimethyl 2‐oxocyclohexane‐1, 3‐dicarboxylate. Issue 5 (13th September 2013) - Jahangiri, Amita; Fleckhaus, Andre; Lidin, Sven; Strand, Daniel
<x xml:space="preserve">Abstract</x> Two polytypic modifications of (1R, 3S)‐dimethyl 2‐oxocyclohexane‐1, 3‐dicarboxylate intergrow to form allotwins. One phase shows monoclinic symmetry, Cc, while the other is orthorhombic Pmc21. The structures may be considered as two different modes of superstructure ordering of an underlying, disordered structure. Considered in the same metrically orthorhombic unit cell a = 37.8883, b = 4.7233, c = 11.6835 Å, the two can be conveniently distinguished by their non‐standard centering, Cc being represented as Xc with the centering vectors (0 0 0); (½ 0 ½); (¼½¾); (¾½¼); and Pmc21 as Xmc21 with the centering vectors (0 0 0); (½ 0 0). The difference between the allotwin domains lies only in the relationship between next‐nearest neighbors along the stacking direction 100 and hence the conformations and packing efficiencies are identical for both phases and all three domains. The stacking sequences for the two phases correspond to ABAB for the orthorhombic stacking and ABA′B′/AB′A′B for the two (equivalent) monoclinic stackings. The monoclinic phase dominates comprising ca 80% of the total volume. Within the monoclinic phase, the ratio between the two possible orientations is highly unbalanced (6:1) indicating relatively large domains. The allotwinning detected in this sample may appear exotic in molecular compounds, but we suggest that the rarity of such examples in the literature is a reflection of the paucity of software that can identify and handle such cases. It is easy to overlook the possibility that a complex diffraction pattern originates from allotwinning and assume that normal mono‐component twinning is the cause. The underlying mechanism in this case is the formation of two‐dimensional layers of molecules that allow for two equivalent, but in terms of absolute geometry, different, ways of stacking.